IMPLEMENTASI STANDAR ISI PENDIDIKAN AGAMA ISLAM (PAI) PADA SMP (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2017)
AbstractSince the enactment of Permendiknas (Regulation of Minister of National Education) No. 22 regarding the contents standard (SI), in its implementation it still faces various problems and obstructions, esspecially in PAI learning. Among the indicators is, the teachers of Islamic religious education (GPAI) find a difficulty in understanding both the SI document and its implementation. In general, teachers also face difficulty in developing the syllabus, especially in formulating the indicators. The study on SI implementation at SMP (Junior High School) is to answer the question on how is GPAI capability in planning the learning implementing the learning, doing the assessment on PAI learning as well as the obstructing factor in PAI learning. Among the finding of such study shows that GPAI capability in planning and implementing the learning is ini fair category. This is affected by the limitation of GPAI understanding on SI document, in syllabus development as well as RPP composing. The assessment procedure on PAI learning in general refers to the Permendiknas no. 22 of 2006, but generally GPAI faces difficulty ini doing the assessment on good behaviour since there is no assessment format yet.Â
Keywords: contents standard; Islamic religious education